Sediment quality assessments in relation to socio-economic development in Kampung Tekek, Tioman Island, Pahang during survey in August 2015 - Sabuti, Asnor Azrin; Miskon, Mohd Fuad; Nik Shirajuddin, Nik Hani Shahira; Abdul Razak, Nur Sakinah; Kassim, Zaleha (2018)
The study to identify the sediment quality changes affected by the increasing human activities along the coastal environment in Kampung Tekek, Tioman Island has been conducted in August 2015. In total, 15 surface sediment samples were collected from three transects in the bay of Kampung Tekek to be analyzed with particle size analyzer (PSA) and loss on ignition (LOI) methods. The results demonstrates good relationship between grain size classification, sediment sorting, skewness and kurtosis which shows differences between the coarser grain and poorly sorted zone up to the finest grain and best sorted zone. However, the highest percentages of sediment composition were recorded to be sand content (23 to 64%) with a mean of 48%, followed with silt content (29 to 68%) with a mean of 43%. The total organic matter (TOM) were ranged from 4.88 to 14.15% with a mean value of 7.61%. This sediment texture contains mostly fine and medium silts could expose potent threat to the coral reefs in the bay of Kampung Tekek due to sedimentation and higher partitioning of contaminants in sediment.